Overview of Olestra: A New Fat Substitute - Richard Hunt; Nora L Zorich; Alan BR Thomson (Canadian Journal of Gastroenterology)
Olestra is a mixture of hexa-, hepta- and octa-esters formed from the reaction of sucrase and long chain fatty acids isolated from edible oils. Olestra has properties similar to those of traditional triglycerides but is not hydrolyzed by pancreatic lipases and, therefore, serves as a noncaloric replacement for fats in the diet. The safety of olestra has been established in over 100 studies in seven different species of animals, with confirmatory safety data coming from approximately 75 human studies; consumption of olestra at levels typical for savoury snacks does not result in reports of gastrointestinal problems in humans. This is consistent with the results of studies of the physiological and morphological effects of olestra in animals and in humans. It is anticipated that olestra will be available in Canada in the near future. Patients will soon be asking their physicians about its use. This article provides an overview of olestra.